2013
DOI: 10.1051/0004-6361/201321147
|View full text |Cite
|
Sign up to set email alerts
|

A portrait of the extreme solar system object 2012 DR30

Abstract: ABSTRACT2012 DR 30 is a recently discovered solar system object on a unique orbit, with a high eccentricity of 0.9867, a perihelion distance of 14.54 AU, and a semi-major axis of 1109 AU, in this respect outscoring the vast majority of trans-Neptunian objects (TNOs). We performed Herschel/PACS and optical photometry to uncover the size and albedo of 2012 DR 30 , together with its thermal and surface properties. The body is 185 km in diameter and has a relatively low V-band geometric albedo of ∼8%. Although the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 45 publications
7
43
0
Order By: Relevance
“…Near-Earth asteroids Müller et al (2012) [M12] (101955) Bennu Müller et al (2017) [M13] (308625) 2005 YU55 Müller et al (2017) [M14] (99942) Apophis Müller et al (2017) [M17] (162173) Ryugu Centaurs and transneptunian objects Duffard et al (2014) [D14] 16 Centaurs Fornasier et al (2013) [F13] Kiss et al (2013) [K13] 2012 DR30 Lellouch et al (2010) [L10] (136108) Haumea Lellouch et al (2013) [L13] Lellouch et al (2016) [L16] Pluto+Charon Lim et al (2010) [LIM10] (136472) Makemake, (90482) Orcus Mommert et al (2012) [MM12] 18 plutinos Müller et al (2010) [M10] Vilenius et al (2012) [V12] 19 classical transneptunian objects Vilenius et al (2014) [V14] 18 classical transneptunian objects Vilenius et al (2018) [V18] 1995 SM 55, 2005RR 43, 2003UZ 117, 2003OP 32, 2002TX 300, 1996TO 66, 1999CD 158, 1999 The following parameters are also extracted from the .csv files obtained by these functions: H, JPL radius, albedo, and slope parameter. In those cases when JPL recognizes the target as a comet and not an asteroid, T-mag (Comet's approximate apparent visual total magnitude), M1 (Total absolute magnitude) parameters are extracted and used.…”
Section: Jpl Horizons Datamentioning
confidence: 99%
“…Near-Earth asteroids Müller et al (2012) [M12] (101955) Bennu Müller et al (2017) [M13] (308625) 2005 YU55 Müller et al (2017) [M14] (99942) Apophis Müller et al (2017) [M17] (162173) Ryugu Centaurs and transneptunian objects Duffard et al (2014) [D14] 16 Centaurs Fornasier et al (2013) [F13] Kiss et al (2013) [K13] 2012 DR30 Lellouch et al (2010) [L10] (136108) Haumea Lellouch et al (2013) [L13] Lellouch et al (2016) [L16] Pluto+Charon Lim et al (2010) [LIM10] (136472) Makemake, (90482) Orcus Mommert et al (2012) [MM12] 18 plutinos Müller et al (2010) [M10] Vilenius et al (2012) [V12] 19 classical transneptunian objects Vilenius et al (2014) [V14] 18 classical transneptunian objects Vilenius et al (2018) [V18] 1995 SM 55, 2005RR 43, 2003UZ 117, 2003OP 32, 2002TX 300, 1996TO 66, 1999CD 158, 1999 The following parameters are also extracted from the .csv files obtained by these functions: H, JPL radius, albedo, and slope parameter. In those cases when JPL recognizes the target as a comet and not an asteroid, T-mag (Comet's approximate apparent visual total magnitude), M1 (Total absolute magnitude) parameters are extracted and used.…”
Section: Jpl Horizons Datamentioning
confidence: 99%
“…To do this, we follow the same methodology as that used in previous studies of dynamically unstable objects (e.g., Horner et al 2004a;Horner & Lykawka 2010a;Kiss et al 2013;Pál et al 2015) and follow the evolution of a suite of clones of Chariklo backward in time for a period of 1 Gyr. By following the evolution of a large population of Chariklo clones, we can obtain a statistical overview of the object's potential past history.…”
Section: Chariklomentioning
confidence: 99%
“…Those were included as such, as well as previous Spitzer results (Stansberry et al 2008;Brucker et al 2009) on four objects not observed by Herschel. Finally Kiss et al (2013a) presented a portrait of the newly discovered and yet unclassified object 2012 DR 30 , 4 When the data could not constrain η, a mean η = 1.20 ± 0.35 (Stansberry et al 2008) was adopted to derive diameters and albedos.…”
Section: Published η Valuesmentioning
confidence: 99%